2008
DOI: 10.1124/jpet.108.136630
|View full text |Cite
|
Sign up to set email alerts
|

N,N′-Alkane-diyl-bis-3-picoliniums as Nicotinic Receptor Antagonists: Inhibition of Nicotine-Evoked Dopamine Release and Hyperactivity

Abstract: The current study evaluated a new series of N, analogs with C 6 -C 12 methylene linkers as nicotinic acetylcholine receptor (nAChR) antagonists, for nicotine-evoked [ 3 H]dopamine (DA) overflow, for blood-brain barrier choline transporter affinity, and for attenuation of discriminative stimulus and locomotor stimulant effects of nicotine. bAPi analogs exhibited little affinity for ␣4␤2* (* indicates putative nAChR subtype assignment) and ␣7* high-affinity ligand binding sites and exhibited no inhibition of DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 37 publications
(45 reference statements)
4
62
1
Order By: Relevance
“…Mechanisms that govern cue effects in drug discrimination are often similar to mechanisms that govern the reinforcing effects of a particular compound (Schuster et al, 1981), although dissociation between these two effects have been observed. For example, the nAChR antagonist N, picolinium dibromide, which has been reported to selectively inhibit ␣6␤2-containing nAChRs, effectively attenuates nicotine self-administration without blocking nicotine cue effects in drug discrimination assays (Neugebauer et al, 2006;Dwoskin et al, 2008). This dissociation suggests that nicotine drug discrimination and self-administration may be governed by separate underlying neurochemical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that govern cue effects in drug discrimination are often similar to mechanisms that govern the reinforcing effects of a particular compound (Schuster et al, 1981), although dissociation between these two effects have been observed. For example, the nAChR antagonist N, picolinium dibromide, which has been reported to selectively inhibit ␣6␤2-containing nAChRs, effectively attenuates nicotine self-administration without blocking nicotine cue effects in drug discrimination assays (Neugebauer et al, 2006;Dwoskin et al, 2008). This dissociation suggests that nicotine drug discrimination and self-administration may be governed by separate underlying neurochemical mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, bPiDDB is a selective, noncompetitive inhibitor of α6β2* nAChRs; bPiDDB inhibits [ 3 H]-nicotine and [ 3 H]-MLA binding (α4β2* and α7* nAChRs, respectively) only at high concentrations (>10 µM; Dwoskin et al, 2008) and decreases nicotine self-administration in rats. Furthermore, bPiDDB (1 µM) produced only 15% and 12% inhibition of acetylcholine (1 mM) -induced current at ganglionic-type α3β4 nAChRs and muscle-type α1β1εδ nAChRs, respectively, expressed in Xenopus oocytes (unpublished data).…”
Section: Monoquaternary Ammonium Salts Derived From N-methylnicotimentioning
confidence: 92%
“…It should be noted that when administered peripherally, several bis-quaternary ammonium antagonists, including bPiDDB, specifically decreased nicotine self-administration and reinstatement of nicotine seeking in rats, providing proof of concept of this representative class of drug as a new pharmacotherapy for nicotine addiction. Additional behavioral studies in the rat have been carried out on other structurally related N,N ′-alkane-diyl-bis-3-picoliniums (Dwoskin et al, 2008; Wooters et al, 2011). …”
Section: Monoquaternary Ammonium Salts Derived From N-methylnicotimentioning
confidence: 99%
“…The interaction of losartan and PD123319 with α4μ2* and α7* nAChRs was evaluated in [ 3 H]nicotine and [ 3 H]methyllycaconitine binding assays, respectively, using a previously described method [45]. Membrane suspensions (100-140 μg protein/100 μl) were prepared from whole brain (excluding cortex and cerebellum) and incubated for 60 min (250 μl final volume) at room temperature in tubes containing losartan (1 nM-1 mM) or PD123319 (1 nM-1 mM) with either 3 nM [ 3 H]nicotine or 3 nM [ 3 H]methyllycaconitine.…”
Section: Methodsmentioning
confidence: 99%